MAGNETO-OPTIC PROPERTIES AND OXIDATION/REDUCTION OF ULTRATHIN MAGNETIC FILMS: FE FILMS ON Pt(111) - T.-U. Nahm (Universitas Gadjah Mada, 2007)
We have investigated magneto-optic properties of ultrathin Fe films grown on Pt(111) surfaces by using the in situ surface magneto-optic Kerr effect (SMOKE) and X-ray photoelectron spectroscopy (XPS). SMOKE measurements show that the Fe layers are not ferromagnetic when the film is thinner than approximately 4.5 MLs (monolayers), but the in-plane magnetization is present for a 4.1 ML Fe film on Pt(111) annealed at 550 K. Upon post-annealing at 770 K, a 9.2 ML Fe film does not show any Kerr signal, while a 6.3 ML Fe film has the in-plane Kerr signal with increased coercivity. The oxidation and reduction of ultrathin Fe films have also been studied by using XPS. Upon an oxygen exposure of 300 Langmuir at a film temperature of 873 K, the Fe layers were mostly oxidized as Fe3O4. When the Fe films were exposed to the same amount of oxygen at room temperature, a partial oxidation as Fe3O4 was observed for a 3 ML Fe film, while there was no oxidation for a 2 ML Fe film. On heating the 873 K oxidized films, Fe3O4O was reduced to FeO, and even the decomposition was observed. Underlying reasons for these chemical changes of Fe and iron-oxide films are discussed.